1999
DOI: 10.1046/j.1464-410x.1999.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol and its metabolite acetaldehyde on responses of the rat bladder

Abstract: Ethanol did not affect resting tension but acetaldehyde and ethanol suppressed bladder muscle contractions. However, direct acetaldehyde-stimulation may release histamine and enhance contractility. This suggests that chronic alcoholism rather than acute intoxication is more likely to provoke urinary retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…An increased ethanol concentration in the bladder wall signi¢-cantly increases the bladder capacity and decreases micturition pressure [Yokoi et al, 1996] by impairing detrusor contractility. Similar results were obtained in a rabbit model [Ohmura et al, 1997] and in vitro experiments of isolated rat urinary bladder [Kim et al, 1999]. As intravesical ethanol can be used as a quantitative measure for bladder hyperpermeability [Monga et al, 2001], the initial e¡ect of vanilloids may partially be due to an impaired detrusor contractility following the penetration of ethanol in the bladder wall.…”
supporting
confidence: 79%
“…An increased ethanol concentration in the bladder wall signi¢-cantly increases the bladder capacity and decreases micturition pressure [Yokoi et al, 1996] by impairing detrusor contractility. Similar results were obtained in a rabbit model [Ohmura et al, 1997] and in vitro experiments of isolated rat urinary bladder [Kim et al, 1999]. As intravesical ethanol can be used as a quantitative measure for bladder hyperpermeability [Monga et al, 2001], the initial e¡ect of vanilloids may partially be due to an impaired detrusor contractility following the penetration of ethanol in the bladder wall.…”
supporting
confidence: 79%
“…It is known that acute ethanol intoxication can cause urinary retention in benign prostatic hyperplasia [17]. In animal studies, the mechanism of urinary retention induced by ethanol partly showed that ethanol significantly impaired detrusor contractility in vivo and in vitro [18][19][20]. Several in vitro studies have revealed that ethanol had significant effect on both contractility and relaxation of rabbit corpus cavernosal smooth muscle (CCSM) [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol has both chronic and acute effects on the body. Animal studies on stimulated bladder muscle strips reported reduced contractility of the detrusor and urethra with acute administration of ethanol 20,21 , while studies on chronic exposure have shown both increased and decreased contractility of the detrusor muscle 22,23 . Acute alcohol consumption causes a transient decrease in circulating testosterone levels 24 , and an increase in circulating oestrogens in men 25 , and sex hormones have been shown to cause relaxation of certain smooth muscle types by suppressing calcium influx 26 .…”
Section: Discussionmentioning
confidence: 99%